A novel soft-rigid wheeled crawling robot with high payload and passing capability. Issue 11 (8th November 2022) - Jia, Jiangming; Cheng, Peilin; Ye, Yuze; Xie, Qizhi; Wu, Chuanyu
Abstract: Soft crawling robots have been significantly studied in recent decades. However, moving in amphibious environment, high payload capability, and passing through complex ground have always been challenges for soft crawling robots. For these problems, this article presents an amphibious soft-rigid wheeled crawling robot (SRWCR) consists of a soft-rigid body actuated by two soft pneumatic actuators (SPAs), four wheels, and four annular soft bladders (ASBs) as brakes. By programming the actuation sequences of the two SPAs and four ASBs, SRWCR can achieve two basic modes of locomotion: linear motion and turning. Based on the energy conservation law, we have developed analytical models to interpret the static actuation performance of SPA, including linear and bending deformations. Furthermore, with the help of fast response and waterproof of SPA and ASB, SRWCR can achieve a linear speed of 14.97 mm/s, a turning speed of 5.63°/s, and an underwater locomotion speed of 13 mm/s, which demonstrates the excellent locomotion performance of SRWCR in amphibious environment. In addition, SRWCR can also achieve multiple impressive functions, including carrying a payload of 2 kg at the moving speed of 11.18 mm/s, passing through various complex ground such as the grass ground and sand ground, and so on, obstacle navigation in confined space. Compared with the existing soft crawling robots, with the help of the soft-rigid body and wheeled structure, SRWCR has the best payload and passing capability, which indicates the potential advantage of SRWCR in the design of functional robots.